O consumo de música regional como mediador da identidade - Dias, Valton Neto Chaves (2008)
This essay tries to understand how the Rio Grande do Sul identity is built concerning two kinds of regional music: rural music and tchê music .In the means of communication these styles are presented as rivals. They oppose the countryside to the city and the tradition to the modernity. This research is based in a case study with theory and methodological beginning in Latin American culture studies through the perspective of the cultural use offered by García Canclini . For the performance of this research were used as mediation of the familiar daily and cultural competence suggested by Martín Barbero. It was verified during the process of the culture establishment in Rio Grande do Sul by the public dominion by the Gaucho traditionalist movement and by the means of communication pass the use of different kinds. It can be important to the identity definition of these consumers. In this way it is possible to analyze the use of these musical kinds in daily routine. It was observed the contradictory and complemented tendencies: The use while distinction and communication (García Canclini, 1996). In this way it is available that social groups face each other and be competitors but in other way the contradiction between the cult and popular, modern and traditional is used to join and communicate different experiences. Concluding, it is understood that in the articulation between social position and cultural use is possible to analyze and understand the constitution of the identities in contemporary.